Analysis of the political law of centralization of state authority in law number 17 of 2023 on health: A normative legal study - Ida Bagus Gede Adiguna Wibawa; Imam Ropii (Journal of Law Science, 2026)
This article examines the political law underlying the centralization of state authority in Law Number 17 of 2023 on Health. The enactment of this law marks a significant shift in Indonesia’s health legal framework, particularly through the strengthening of the central government’s role in regulating, supervising, and controlling the national health system. The objective of this article is to analyze the legal policy orientation behind this centralization and to assess its implications for health governance, professional autonomy, and adherence to rule-of-law principles. This study employs a normative legal research method using statutory, conceptual, and historical approaches. Primary legal materials consist of Law Number 17 of 2023 and related regulations, while secondary materials include scholarly books and journal articles on political law and health law. The findings indicate that centralization in the Health Law reflects the state’s policy to improve regulatory effectiveness, policy coherence, and equitable health service delivery. However, this legal policy also raises normative and operational challenges, particularly regarding the distribution of power, the independence of health professionals, and institutional accountability. Operational accountability indicators identified include transparency requirements, objection mechanisms, policy audits, and judicial oversight, which are essential to ensure that centralization does not compromise the rule of law or professional autonomy. Finally, the study identifies priority research agendas to strengthen understanding of centralized health governance, such as analyzing conflicts between regulatory norms, reviewing Constitutional Court or Supreme Court decisions on health authority, and conducting comparative studies with other countries. The article concludes that while Law Number 17 of 2023 strengthens national health governance, balanced and conditional centralization supported by legal safeguards is necessary to achieve both effectiveness and normative compliance.